Natron glass beads reveal proto-Silk Road between the Mediterranean and China in the 1st millennium BCE - Lü, Qin-Qin (Sci Rep, 2021)
Natron-based glass was a vital part of material culture in the Mediterranean and Europe for nearly two millennia, but natron glass found elsewhere on the Eurasian Continent has not received adequate discussion, despite its influence on ancient Asian glass. Here we present a new interpretation of natron glass finds from both the West and the East. After establishing the compositional types and technological sequence of Mediterranean natron glass (eighth-second century BCE) using trace elements, we report the analysis of a mid-1st millennium BCE glass bead from Xinjiang, China, which was likely made with Levantine raw glass, and identify common types of stratified eye beads in Eurasia based on a compositional and typological comparison. Combining these findings, we propose that a considerable number of Mediterranean natron glass products had arrived in East Asia at least by the fifth century BCE, which may have been a contributing factor in the development of native Chinese glass-making. The swift diffusion of natron glass across Eurasia in the 1st millennium BCE was likely facilitated by a three-stage process involving maritime and overland networks and multiple forms of trade and exchange, indicating a highly adaptable and increasingly efficient transcontinental connection along the ‘Proto-Silk Road’.